Letramento : da aquisição da escrita à posição de sujeito-autor - Oliveira, Fabiano Batista de (2017)
Many are the ways in which we seek to study the written evidence in textual medium level students productions. And it always brings the need to establish concepts such as literacy, literacy, subject, author and authorship. For such pursue a path that seemed the most feasible, show evidence of authorship through the literacy process. The aim was to examine the texts looking for brands that inform traces of other voices now transformed in the voice of the student, now author (not in Foucault's sense), but in the Syrian Possenti line. Here, on these pages, authorship is related to the announcer concepts (who is responsible for what it says) and uniqueness (style, particular way to do this in the text). The latter relationship is the basis of our project, which unites the knowledge of the student with the knowledge shared world after contact with other discourses. As theoretical references resorted to Tfouni, Orlandi, Foucault, Bakhtin, Possenti and many others who gave their contributions on the question of authorship